2014
DOI: 10.1111/ppl.12156
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of GPI-anchored lipid transfer proteins in the development of seed coats and pollen inArabidopsis thaliana

Abstract: The non-specific lipid transfer proteins (nsLTPs) constitute a large protein family specific for plants. Proteins from the family are found in all land plants but have not been identified in green algae. Their in vivo functions are still disputed although evidence is accumulating for a role of these proteins in cuticle development. In a previous study, we performed a co-expression analysis of glycosylphosphatidylinositol (GPI)-anchored nsLTPs (LTPGs), which suggested that these proteins are also involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 35 publications
3
83
0
Order By: Relevance
“…With regards to the extracellular transport of suberin, the identification of the putative lipid transporter, LTPG5, being coexpressed with suberin forming tissues, as well as downregulated in myb107, is particularly interesting. In previous work, LTPG1 was shown to be active in the extracellular transport of cuticular lipids in Arabidopsis (Debono et al, 2009), while LTPGs have recently been shown to function in the development of both seed coat and pollen apoplastic barriers (Edstam and Edqvist, 2014). It is therefore likely that LTPG5 is involved in suberin deposition in the seed coat of Arabidopsis in a function mediated through MYB107 activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to the extracellular transport of suberin, the identification of the putative lipid transporter, LTPG5, being coexpressed with suberin forming tissues, as well as downregulated in myb107, is particularly interesting. In previous work, LTPG1 was shown to be active in the extracellular transport of cuticular lipids in Arabidopsis (Debono et al, 2009), while LTPGs have recently been shown to function in the development of both seed coat and pollen apoplastic barriers (Edstam and Edqvist, 2014). It is therefore likely that LTPG5 is involved in suberin deposition in the seed coat of Arabidopsis in a function mediated through MYB107 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Genes potentially linked with suberin biosynthesis found to be downregulated in both myb9 and myb107 seeds include those encoding SUS (the putative suberin synthase); an SGNH hydrolase-type esterase superfamily protein (likely involved in lipid metabolic processes; Li-Beisson et al, 2013); CASP-LIKE PROTEIN 1B2 (CASPL1B2, showing strong homology to CASP proteins involved in casparian strip metabolism); LACCASE3 (a member of the laccase family of which LACCASE4 has been demonstrated to be involved in lignin metabolism; Zhao et al, 2013;Schuetz et al, 2014); DIHYDROFLAVONOL 4-REDUCTASE-LIKE1 (DFR-like1; involved in phenylpropanoid metabolism and previously linked to pollen wall development and seed production (Lallemand et al, 2013); and LUPEOL SYNTHASE5 (LUP5; a multifunctional triterpene synthase; Ebizuka et al, 2003). While genes downregulated in myb107 seeds (but not myb9 seeds) encode GPAT5 and ASFT (known to act in suberin formation); 3-KETOACYL-COA SYNTHASE17 (KCS17; a very-long-chain fatty acid synthase); 4-COUMARATE:COA LIGASE5 (4CL5; involved in phenylpropanoid metabolism); and GLYCOSYLPHOSPHATIDYLINOSITOL-ANCHORED LIPID PROTEIN TRANSFER5 (LTPG5; a homolog to the lipid transporter LTPG1; Debono et al, 2009;Edstam and Edqvist, 2014). Finally, the gene encoding CYP86A1, characterized for its involvement in suberin monomer biosynthesis, was downregulated in myb9 seeds (but not myb107 seeds).…”
Section: Myb107 and Myb9 Are Required For Suberin-associated Gene Expmentioning
confidence: 99%
“…In general, CFC amounts to 1.6-3.02% of the total weight of brown rice at 14% moisture and plays a major role in rice storage quality [4]. Crude fat content of rice, including palmitic acid (16:0), stearic acid (18:0), oleic acid (18:1), linoleic acid (18:2, 18:3) and several other components, are important factors that determine rice appearance and eating quality [5]. It was reported that alteration of lipid content in rice seed resulted in chalky endosperm.…”
Section: Introductionmentioning
confidence: 99%
“…NsLTPs facilitate the transportation of fatty acids, phospholipids, and steroids between membranes, which play diverse roles in various biological processes, such as cutin biosynthesis in pollen development, stress response, plant signaling and seed maturation [16,17]. In Arabidopsis thaliana, a GPI-anchored lipid transfer protein was reported to be involved in the development of seed coats and pollen [18]. Two nsLTPs were up-regulated during slow drying treatment in barley and several nsLTPs were identified from dehydration-stressed tissues of cassava [19].…”
Section: Introductionmentioning
confidence: 99%
“…Anyway, with systematic approaches it will definitely be possible to significantly advance our knowledge in a few years from now. Mosses and liverworts are emerging as models for studies on the assembly, function and evolution of the plant cuticle (31,85,86 …”
Section: Structural Plasticity Of Ltpsmentioning
confidence: 99%